Habituation responses in wild reindeer exposed to recreational activities - Reimers, Eigil; Røed, Knut H.; Flaget, Øystein; Lurås, Eivind (Rangifer, 2010)
Displacement is the effect most often predicted when recreational activities in wild reindeer (Rangifer tarandus tarandus) areas are discussed. Wild reindeer in Blefjell (225 km2) are exposed to humans more frequently than in Hardangervidda (8200 km2), from which the Blefjell herd originate. We recorded fright and flight response distances of groups of reindeer in both herds to a person directly approaching them on foot or skis during winter, summer, and autumn post-hunting and rutting season in 2004-2006. The response distances sight, alert, flight initiation and escape were shorter in Blefjell than in Hardangervidda while the probability of assessing the observer before flight tended to be greater in Blefjell. To test whether these results could be due to habituation or genetic influence of semi-domestic reindeer previously released in the Blefjell region, we compared the genetic variation of the Blefjell reindeer with previously reported variation in semi-domestic reindeer and in the wild reindeer from Hardangervidda. Microsatellite analyses revealed closer genetic ancestry of the Blefjell reindeer to the wild Hardangervidda reindeer and not to the semi-domestic reindeer at both the herd and the individual level. We conclude that the decreased flight responses in Blefjell reindeer appear to be a habituation response to frequent human encounters rather than traits inherited from a semi-domestic origin.